72 Jam Pertama Pendekatan Komunikasi Risiko Untuk Kesiapsiagaan Bencana - Fajar Dwi Putra (Al-MUNZIR, 2023)
Disasters are caused by the interaction of biophysical systems, human systems, and the built environment. Disaster management with a lack of understanding and context of risk communication. When a major disaster occurs, recovery requires a massive infusion of external public and private resources, but what happens is that conditions are highly unequal, and likely to produce many of the pre-existing inequities in exposure and vulnerability. This research focuses on the first 72 hours of disaster relief through effective communication in the case of the 13 June 2022 tornado in Yogyakarta. The purpose of this study is to provide education about the first 72 hours that must be carried out in handling disaster cases through an effective and central communication channel. The research method used is qualitative, existential phenomenology and the paradigm built is constructivism. The findings in the field show that the people of Yogyakarta still lack knowledge about how to communicate effectively in dealing with disasters such as a lack of evacuation training, minimal communication tools, minimal evacuation route maps, even in the context of a tornado disaster, no residents know what to do. to do and to whom they should communicate first. The potential impact of ineffective communication; more and more victims, disaster losses increased partly because the way to design and build communication is wrong and not on target. Many people speculate about the causes of disasters, the minimal contribution of society to increased exposure to hazards often results in damage to environmental resources such as the collapse of people's houses and damage to public facilities. Initial disaster failure; identifying communication lines to ensure evacuation of highly vulnerable environments should be known before disaster. Improvement of long-term communication lines needs to be improved by mapping community communication patterns, communication tools and who is the first person to contact.Keywords: Risk Communication, Disaster Communication, Disaster Evacuation, Communication Lines